Study on the mechanism of urban morphology on river cooling effect in severe cold regions - Guo, Fei; Xu, Sheng; Zhao, Jun; Zhang, Hongchi; Liu, Lijuan; Zhang, Zhen; Yin, Xinyuan (Frontiers in Public Health, 2023)
In the context of global warming, urban climate problems such as heat waves, urban heat islands and air pollution are becoming increasingly prominent, and the cooling effect of rivers is an effective way to mitigate urban hot climate. This study investigates the surrounding urban area of the Hun River in Shenyang, a severe cold region of China, by calculating satellite inversion surface temperature and urban morphology data, and explores the cooling effect of rivers using linear regression models and spatial regression models. The results show that 1) water bodies have a cooling effect on the surrounding environment, with the farthest cooling distance being 4000 m, but the optimal cooling distance being 2500 m. 2) Urban morphological factors are closely related to surface temperature LST, with NVDI (Normalized vegetation index) and BD (building density) having the most obvious effect, with NVDI being negatively related to LST and BD being positively related to LST. 3) The urban thermal environment can be improved and the heat island effect mitigated through measures such as increasing urban vegetation cover and reducing building density, and these findings can provide data references and case studies to support urban planning and development departments.